Two ways to save neem seed - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
It is now officially impossible to claim to have invented something which has been in public use for centuries. On 10 May 2000, the European Patent Office (EPO) revoked a patent which had been granted to the United States of America and...